Clearcut [videorecording (DVD)] : the story of Philomath, Oregon - Richardson, Peter (Filmmaker) (Clearcut Productions, 2006)
In 2002, the small town of Philomath, Oregon, was thrown into the national spotlight when the Clemens Foundation, under the leadership of Steve Lowther, decided to withdraw the college scholarships that the foundation had guaranteed to all Philomath High School graduates. In this film, the events leading up to the decision are related by Lowther, school district officials, teachers, students, and members of the community. As the participants tell their stories, the real story that emerges is the struggle within a rural Oregon town for its cultural identity.